Metabolic activity of Glomus intraradices in Arum- and Paris-type arbuscular mycorrhizal colonization - van Aarle, Ingrid M (The New phytologist, 2005)
Colonization of two plant species by Glomus intraradices was studied to investigate the two morphological types (Arum and Paris), their symbiotic interfaces and metabolic activities. Root pieces and sections were stained to observe the colonization and metabolic activity of all mycorrhizal structures. There were no growth responses observed in the plants caused by mycorrhizal symbiosis. The two morphological types had a similar percentage of root colonized, but the Arum-type had higher metabolic activity. Most of the mycorrhizal structures (88%) showed succinate dehydrogenase activity; about half showed acid phosphatase activity; and a small percentage showed alkaline phosphatase activity. Phosphatase activity was highest in arbuscules and low in intercellular hyphae in the Arum-type colonization. In the Paris-type, hyphal coils and arbusculate coils showed a similar intermediate percentage of phosphatase activity. We conclude that acid phosphatase is more important than alkaline phosphatase in both colonization types. We discuss the possibility that, whereas arbuscules in Arum-type are the main site for phosphorus release to the host plant, both the hyphal and arbusculate coils may be involved in the Paris-type